2020
DOI: 10.21203/rs.2.14809/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of diet-associated responses in two rice planthopper species

Abstract: Background: Host adaptation is the major determinant of insect diversification. However, knowledge of different host ranges in very close-related species remains scarce. The brown planthopper (Nilaparvata lugens, BPH) and small brown planthopper (Laodelphax striatellus, SBPH) are the most destructive insect pests belonging to Delphacidae. These two species differ in the host range (SBPH can well colonize on rice and wheat plants, while BPH survive on rice plants only), but the underlying mechanism still remain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 50 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Our previous study has analysed the gut gene expression patterns of BPH and SBPH on rice and wheat plants (Huang et al ., 2020). To explore the potential mechanism underlying the different host adaptation in three planthopper species, we further analysed the responses of WBPH to rice and wheat hosts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study has analysed the gut gene expression patterns of BPH and SBPH on rice and wheat plants (Huang et al ., 2020). To explore the potential mechanism underlying the different host adaptation in three planthopper species, we further analysed the responses of WBPH to rice and wheat hosts.…”
Section: Resultsmentioning
confidence: 99%
“…It is previously demonstrated that genes associated with sugar transporters and heat shock proteins showed similar expression trends; while most genes were reciprocally regulated between BPH and SBPH (Huang et al ., 2020). In this study, we found that sugar transporters (belonged to type I response genes) and heat shock proteins (belonged to type I or type III response genes) showed similar expression variation in three planthoppers, indicating that these genes played conserved roles in coping with host changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations